2013
DOI: 10.1186/1472-6882-13-340
|View full text |Cite
|
Sign up to set email alerts
|

Usage patterns and adverse experiences in traditional Korean medicine: results of a survey in South Korea

Abstract: BackgroundAlthough traditional medicine (TM) in South Korea is included in the national health care system, it is considered complementary and alternative medicine (CAM), and not mainstream medicine. Therefore, the lack of statistical data regarding the usage and adverse experiences of traditional Korean medicine (TKM) makes difficult to understand the current status of TM. In this study, we aimed to report usage patterns and adverse experiences on TKM targeting consumers in South Korea.MethodsA total of 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…Although the entire population is covered by medical insurance and many people were familiar with various modalities as the major form of health care [15], others were opposed to TKM because of the lack of scientific evidence regarding its practices, adverse effects resulting from treatment, or because of the financial burden [5,12]. Nevertheless, we found that two-thirds of our sample population used some type of TKM therapies in 2011.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Although the entire population is covered by medical insurance and many people were familiar with various modalities as the major form of health care [15], others were opposed to TKM because of the lack of scientific evidence regarding its practices, adverse effects resulting from treatment, or because of the financial burden [5,12]. Nevertheless, we found that two-thirds of our sample population used some type of TKM therapies in 2011.…”
Section: Discussionmentioning
confidence: 58%
“…The questionnaire that we used contained nearly the same checklists as his survey, and we followed his protocols as much as possible. In addition, the socio-demographic ratios among the participants, the age distributions of the participants, and the dates of the year in our survey were similar to those same features in the 2008 survey [12].…”
Section: Comparison Of the 2008 Survey With Our 2011 Surveymentioning
confidence: 52%
See 3 more Smart Citations